PERANCANGAN SISTEM KEAMANAN TAS RANSEL BERBASIS ESP8266 DENGAN NOTIFIKASI MENGGUNAKAN APLIKASI TELEGRAM - Rudi Kristanto; Edy Kurniawan (Universitas Muhammadiyah Ponorogo, 2020)
A backpack is a medium that functions as a storage for various valuables. In general, backpacks that are not equipped with a safety system can make them vulnerable to theft. This research resulted in a security system design to detect the location of the backpack and detect the backpack open by force with a notification using the telegram application. In this backpack security system will use components, namely light sensor (LDR), voltage sensor, ADS1115 module, unblox 6m GPS module, IC ESP8266, external modem, buzzer driver, stepup circuit, buzzer, battery and telegram application. The ESP8266- based backpack security system with notifications using the telegram application has several advantages, namely that it can provide a warning in the form of a buzzer alarm and notification on the teleram application if the backpack is forced to open, can track the position of the backpack in case of theft and if you don't remember the position of the backpack . The results of research on the backpack system are able to work according to predetermined working principles and data analysis is also in accordance with existing calculations.